Adult-Onset Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome on the Basis of Selective IgA Deficiency - Seda Altiner; Alper Ekinci (Hindawi Limited, 2024)
Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis syndrome (PFAPA) is an autoinflammatory disease that is thought to occur with the contribution of genetic and environmental factors, but its etiology has not been clearly elucidated. It is characterized by recurrent attacks with fever, pharyngitis, oral aphthous lesions, and cervical lymphadenopathy, and an increase in the level of serum acute phase reactants is observed during the attacks. Although PFAPA usually begins in childhood, adult-onset cases are also reported in the literature. In the pathogenesis of PFAPA, an increase in the expression of various inflammatory cytokines, especially interleukin-1β (IL-1β), is observed as a result of the increase in inflammasome activity. Selective IgA deficiency (SIgAD) is the most prevalent primary immunodeficiency. Although most SIgAD cases remain asymptomatic and remain undiagnosed, it is known that the risk of mucosal infection is generally increased in SIgAD cases. In addition, the frequency of autoinflammatory diseases is increased in SIgAD cases compared with the general population. We aim to present a case of adult-onset PFAPA and SIgAD coexistence.